Multi-core and many-core SPMD parallel algorithms for construction of basins of attraction - Silveira, Marcos [UNESP]; Gonçalves, Paulo J.P. [UNESP]; Balthazar, José M. [UNESP] (Polish Society of Theoretical and Applied Mechanics, 2019)
Construction of basins of attraction, used for the analysis of nonlinear dynamical systems which present multistability, are computationaly very expensive. Because of the long runtime needed, in many cases, the construction of basins does not have any practical use. Numerical time integration is currently the bottleneck of algorithms used for the construction of such basins. The integrations related to each set of initial conditions are independent of each other. The assignment of each integration to a separate thread seems very attractive, and parallel algorithms which use this approach to construct the basins are presented here. Two versions are considered, one for multi-core and another for many-core architectures, both based on a SPMD approach. The algorithm is tested on three systems, the classic nonlinear Duffing system, a non-ideal system exhibiting the Sommerfeld effect and an immunodynamic system. The results for all examples demonstrate the versatility of the proposed parallel algorithm, showing that the multi-core parallel algorithm using MPI has nearly an ideal speedup and efficiency.
Keywords: Basins of attraction; CUDA; Duffing equation; Immunodynamics; MPI; Sommerfeld effect